Extrudable region parametrical study of 3D printable concrete using recycled glass concrete - Ting, Andrew Guan Heng (2022)
3D concrete printing (3DCP) is gaining much attention due to the absence of formwork, allowing more freedom in the architectural design, and reducing construction costs significantly. The lack of formwork configuration in the 3DCP technique requires the printable concrete to possess self-supporting properties. Furthermore, the yield stress evolution over time caused by the structuration build-up of the cement also allows a larger buildable height of the print. However, before the structuration in the material occurs, the concrete needs to possess high initial yield stress to maintain its shape upon extrusion during the early stage of the printing process. Although it is advantageous to have higher yield stress for the buildability of the concrete, the extrudability of the concrete should also be considered. When the yield stress of the concrete is too high, the pumping effort to cause flow in the concrete becomes too high and the extruded filament displays defects on the surface of the filament. This study aims to study the effects of various material parameters on the concrete extrudability and buildability to determine the extrudable region of the concrete mix design using a graphical approach. The material parameters that are being studied in this research includes aggregates fraction, attapulgite nano-clay content, and aggregates fineness. The results shows that the mix designs at the extrudable limit surface is most optimal for 3D concrete printing as it has the maximum buildability with the extrudable region.